2020
DOI: 10.3390/fib8030019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cooling Methods on the Behavior of Reactive Powder Concrete Exposed to Fire Flame Effect

Abstract: The construction of highly safe and durable buildings that can bear accident damage risks including fire, earthquake, impact, and more, can be considered to be the most important goal in civil engineering technology. An experimental investigation was prepared to study the influence of adding various percentages 0%, 1.0%, and 1.5% of micro steel fiber volume fraction (Vf) to reactive powder concrete (RPC)—whose properties are compressive strength, splitting tensile strength, flexural strength, and absorbed ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
3
3
0
Order By: Relevance
“…According to Hasan et al [41], inserting fibers into a concrete mixture can increase the concrete composite's tensile strength by about 10-15%, compared to standard concrete. Other research found similar results that fibers can prevent brittle failure and enhance the ductility of the concrete [48,52,54].…”
Section: The Effect Of Hdpe Additions To Tensile and Compressive Strengthsupporting
confidence: 64%
See 1 more Smart Citation
“…According to Hasan et al [41], inserting fibers into a concrete mixture can increase the concrete composite's tensile strength by about 10-15%, compared to standard concrete. Other research found similar results that fibers can prevent brittle failure and enhance the ductility of the concrete [48,52,54].…”
Section: The Effect Of Hdpe Additions To Tensile and Compressive Strengthsupporting
confidence: 64%
“…As stated earlier, previous studies have found a relationship between plastics addition influencing concrete's tensile strength and compressive strength [19,21,53] matching those of steel fibers that affected the value of splitting tensile and compressive strength [54], as well as plastic fibers, carbon fibers, and fibers from natural materials, such as flax or other plants. According to Hasan et al [41], inserting fibers into a concrete mixture can increase the concrete composite's tensile strength by about 10-15%, compared to standard concrete.…”
Section: The Effect Of Hdpe Additions To Tensile and Compressive Strengthmentioning
confidence: 62%
“…Sample LH-04 presented greater crack formation throughout the cylinder patterns, which is one of the indicators of the effects of fibers in developing a crack-resistant mechanism and changing the nature of the material from brittle to ductile [97]. These findings support other studies that showed that fibers can prevent brittle failure and improve the ductility of concrete [29,98,99]. Flexural strength is an important parameter in the mechanical properties of concrete; Figure 9 describes these values and percentages.…”
Section: Flexural and Compressive Mechanical Properties Of Concrete W...supporting
confidence: 77%
“…According to Hasan et al [42], inserting fibres into a concrete mixture can increase the strength of concrete composites by about 10-15% of the tensile strength of normal concrete. Several other researchers have found similar results [44][45][46].…”
Section: Tensile and Compressive Strengthssupporting
confidence: 74%